1995
DOI: 10.1007/bf00137782
|View full text |Cite
|
Sign up to set email alerts
|

Partial restoration of fungal and plant species diversity by removal of litter and humus layers in stands of Scots pine in the Netherlands

Abstract: A field experiment was set up in five mature Scots pine (Pinus sylvestris) stands in the Netherlands in order to study the effects of removal of litter and humus on ectomycorrhizal fungi and vegetation of higher plants, bryophytes, and lichens. Lime was also applied as a countermeasure to the removal of surplus cations. Application of lime did not have significant effects on mycorrhizal fungi. Removal of ectorganic material increased species richness of ectomyeorrhizal fungi. The number of fruit bodies was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 9 publications
1
11
0
1
Order By: Relevance
“…Nohrstedt (1994) reported a 30% decrease in sporocarp production by C. cibarius in a central Swedish pine forest after application of 150 kg N ha -1 ammonium nitrate. In addition, it has been shown that removal of the upper organic layers of the forest floor can improve partially sporocarp production by C. cibarius (de Vries et al 1995) and other ECM fungi (Baar and ter Braak 1996). This was attributed to high concentrations of mineral N, primarily ammonium, within the organic layers that are detrimental to fungal growth.…”
Section: Discussionmentioning
confidence: 97%
“…Nohrstedt (1994) reported a 30% decrease in sporocarp production by C. cibarius in a central Swedish pine forest after application of 150 kg N ha -1 ammonium nitrate. In addition, it has been shown that removal of the upper organic layers of the forest floor can improve partially sporocarp production by C. cibarius (de Vries et al 1995) and other ECM fungi (Baar and ter Braak 1996). This was attributed to high concentrations of mineral N, primarily ammonium, within the organic layers that are detrimental to fungal growth.…”
Section: Discussionmentioning
confidence: 97%
“…In each station, buffer areas were marked out. In 27 stations, the litter layer was manually removed, according to various authors (Tyler, 1991;Termorshuizen, 1990;Baar and ter Braak, 1996;De Vries et al, 1995) who had valued the effects of this material on the fruiting process. In Fig.…”
Section: Division Of the Study Areasmentioning
confidence: 99%
“…When litter and humus layers in the secondary Scots pine stands were removed ("sod-cutting"), numbers of species and sporocarps of ectomycorrhizal fungi were enhanced (Baar and Kuper, 1993;Vries et al, 1995). Species composition in sod-cut plots on nonpodsolic sandy soil (Haplic Arenosol, FAO-Unesco, 1988) approached that in primary Scots pine stands on nutrient-poor, non-podsolic sandy soils with thin litter and humus layers.…”
Section: Introductionmentioning
confidence: 99%